Comparative study of the absorption coefficient of Nb metal and its compound. (2021) - Manjula, G.; Rani Roy, Bunty; Jyothsna, S.; Mahesh Kumar, A.; Yadav, Ashok Kumar; Nageswara Rao, A.S.
Abstract: The Extended X-ray absorption fine structure (EXAFS) is used to support the absorption coefficient for Nb metal foil and its compound to be determined at different X-ray energies, which is in the energy range of X-ray is 18.9132–19.6882 keV to most extreme precision. As a result the informational index for Nb metal and its compound remember supreme absorption coefficients for the area of extended x-ray absorption fine structure. Correlation results from the absorption coefficients demonstrates the contrasts between the determined and measured values. The observed values were compared with the theoretical predictions WinXcom and FFAST programs. The results near and exactly above the k-edge show good agreement with theoretical and experimental observations.